2018
DOI: 10.1042/cs20180087
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of gut microbiome and intestinal epithelial barrier dysfunction in patients with high blood pressure

Abstract: Recent evidence indicates a link between gut pathology and microbiome with hypertension (HTN) in animal models. However, whether this association exists in humans is unknown. Thus, our objectives in the present study were to test the hypotheses that high blood pressure (BP) patients have distinct gut microbiomes and that gut–epithelial barrier function markers and microbiome composition could predict systolic BP (SBP). Fecal samples, analyzed by shotgun metagenomics, displayed taxonomic and functional changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
355
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(443 citation statements)
references
References 71 publications
(75 reference statements)
37
355
1
4
Order By: Relevance
“…SCFAs have been demonstrated to exert many beneficial effects on intestinal epithelium, including inhibition of inflammation, and modulation of oxidative stress . Furthermore, an improved barrier function by SCFAs has been reported in vitro, ex vivo, and in animal studies . In agreement with these data, we also found that probiotics, and acetate and butyrate consumption increased mRNA levels of tight junction protein occludin and ZO‐1 in the colon.…”
Section: Discussionsupporting
confidence: 89%
“…SCFAs have been demonstrated to exert many beneficial effects on intestinal epithelium, including inhibition of inflammation, and modulation of oxidative stress . Furthermore, an improved barrier function by SCFAs has been reported in vitro, ex vivo, and in animal studies . In agreement with these data, we also found that probiotics, and acetate and butyrate consumption increased mRNA levels of tight junction protein occludin and ZO‐1 in the colon.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the ratio of the levels of faecal Firmicutes to Bacteroidetes (the F/B ratio) is a useful proxy for classifying the metabolic composition of the microbiome of an individual. Changes in bacteria composition associated with hypertension are followed by alterations in the levels of bacterial metabolic products (Kim, et al , ). This concept is corroborated by data from several studies in hypertensive models that demonstrated higher F/B ratio in affected hosts (Yang, et al , ; Marques, et al , ; Toral, et al , ).…”
Section: Interactions Between the Gut Microbiota And Cvdsupporting
confidence: 56%
“…Furthermore, targeted inhibition of this inflammatory pathway reduces the risk of incident adverse cardiovascular events (Ridker, et al , ). SCFAs, such as butyrate, have received increasing interest in relation to hypertension, and their main effects are modulation of the microbial composition and inflammation reduction (Wang, et al , ; Kim, et al , ). Propionate also exhibits hypotensive effects, possibly via expansion of the splenic Treg cell population (Bartolomaeus, et al , ).…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…Other recent studies may reinforce this hypothesis, reporting a strong relation between hypertension, gut mucosal permeability and altered inflammatory status in rats 11 and humans 41 with hypertension. Kim et al reported significant increases in plasma of intestinal fatty acid binding protein, lipopolysaccharide, and augmented gut-targeting proinflammatory T helper 17 cells in high BP patients, which demonstrated increased intestinal inflammation and permeability in HT subjects 41 . Together with these results, they also observed significant lower levels of plasma butyrate in HT subjects.…”
Section: Scfa In Feces and Plasmamentioning
confidence: 99%